2017
DOI: 10.1177/1744806917719169
|View full text |Cite
|
Sign up to set email alerts
|

Activation and expression of μ-calpain in dorsal root contributes to RTX-induced mechanical allodynia

Abstract: BackgroundCalpain is a calcium-dependent cysteine protease, and inhibition of calpain by pre-treatment with MDL28170 attenuated the rat mechanical allodynia in a variety of pain models. Postherpetic neuralgia (Shingles) is a neuropathic pain conditioned with the presence of profound mechanical allodynia. Systemic injection of resiniferatoxin can reproduce the clinical symptoms of postherpetic neuralgia. In this study, we determined to study whether activation of calpain contributes to cleave the myelin basic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Next, we tested the expression levels of MMP2 and μ‐calpain, which were reported to be involved in the cleavage of MBP 43,44 . After exposure to As, the expression levels of MMP2 and μ‐calpain increased noticeably as compared to the control, with significance in the increment of μ‐calpain expression level, and application of MeCbl in As‐treated group greatly counteracted the increases in μ‐calpain (F (3, 8) = 6.06, p = .02) expression levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, we tested the expression levels of MMP2 and μ‐calpain, which were reported to be involved in the cleavage of MBP 43,44 . After exposure to As, the expression levels of MMP2 and μ‐calpain increased noticeably as compared to the control, with significance in the increment of μ‐calpain expression level, and application of MeCbl in As‐treated group greatly counteracted the increases in μ‐calpain (F (3, 8) = 6.06, p = .02) expression levels.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, a significant upregulated μ‐calpain level was observed in As‐treated animals, accompanied with increased anti‐MBP antibody level in serum and declined mechanical withdrawal threshold, which was in accordance with the result of other researchers. For example, Yuan et al found that μ‐calpain released from Schwann cell contributed to cleave the MBP of dorsal root and was involved in resiniferatoxin‐induced mechanical allodynia 43 . In the case of traumatic brain injury, calpain could degrade MBP into N‐terminal fragments in the ipsilateral cortex and initiate T cell‐dependent secondary structural damage to the adjacent myelin membrane 58 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An Olympus BX51 fluorescence microscope was used to view the sections, and images were obtained using a Qimaging Camera and QCapture software as described before ( Yuan et al, 2017 ). A total of 5–6 sections from the skin or cervical cord were randomly selected in each mouse.…”
Section: Methodsmentioning
confidence: 99%